2022
DOI: 10.1002/stc.3000
|View full text |Cite
|
Sign up to set email alerts
|

Performance and optimal design of base‐isolated structures with clutching inerter damper

Abstract: The performance and optimal design of the base-isolated structure supplemented with clutching inerter damper (CID) subjected to seismic loading are investigated. Because of the nonlinear force-deformation behavior of the CID, the stochastic response of the isolated structure subjected to nonstationary earthquake excitation is obtained using the time-dependent equivalent linearization technique. To investigate the effects of nonstationary earthquake characteristics, the isolated structure's nonstationary respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 50 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…Although the original structure response is greatly reduced, a large deformation induced by the earthquake ground motion will occur on the base foor, thus the superstructure might face collapse risk when experiencing an extremely rare earthquake. Hence, hybrid base isolation systems, which combine isolation bearings and passive dampers, receive increasing attention [7][8][9][10][11] and intend to tackle the challenges of overlarge base deformation of the BIS during extremely rare earthquakes while maintaining or reducing superstructure responses.…”
Section: Introductionmentioning
confidence: 99%
“…Although the original structure response is greatly reduced, a large deformation induced by the earthquake ground motion will occur on the base foor, thus the superstructure might face collapse risk when experiencing an extremely rare earthquake. Hence, hybrid base isolation systems, which combine isolation bearings and passive dampers, receive increasing attention [7][8][9][10][11] and intend to tackle the challenges of overlarge base deformation of the BIS during extremely rare earthquakes while maintaining or reducing superstructure responses.…”
Section: Introductionmentioning
confidence: 99%
“…Clutching inertia dampers have been extensively studied in recent years as a variable‐inertia model. They have been investigated in various seismic structural systems, 9,11,28 base isolation systems, 29,30 TMD systems, 31,32 and rocking systems 33,34 . The authors mainly focus on the research of clutching inertia devices in seismic structural systems 28,35–37 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Wang and Sun further analyzed the performance of the ideal model of the clutching inerter in comparison with the inerter and concluded that the clutching inerter improves the control performance of resonant displacement and peak displacement under sinusoidal and seismic excitations. 10 In addition, the performance of the clutching inerter has also been studied in TMD system, 14,15 base-isolated system 16 and rocking system. 17 However, the clutching inerter was analyzed using the ideal model in most studies and there is still no perfect experimental verification on the performance of a real clutching inerter, although Malaga-Chuquitaype et al 18 conducted relevant tests on a pair of 3D printed clutched inerter, only tests under several low-frequency loads were performed due to the limitation of loading.…”
Section: Introductionmentioning
confidence: 99%